VISUALIZATION TOOLS FOR GROUPOIDS ASSOCIATED TO NONAUTONOMOUS DISCRETE DYNAMICAL SYSTEMS - Mădălina Roxana BUNECI (Fiabilitate şi Durabilitate)
The purpose of this paper is to provide visualization tools for analysis of the family of groupoids associated in [5] to a discrete nonautonomous system.